ANALYSIS OF FACTORS THAT INTO CONSIDERATION FACTORS IN CHOOSING THE CUSTOMER SAVINGS SIMPEDA KALTIM BANK BRANCH SANGATTA - Dwi Priyanto (EKONOMIA, 2013)
Data processing techniques in this study using computational calculation SPSS (Statistical Product and Service Solutions ) because the program has a high enough statistical analysis capabilities as well as the data management system in a graphical environment using descriptive menus and simple dialog boxes , making it easy to understand how operation ( Lewis , 2007: 1 ) .Based on the research results , it can be concluded that the factors that are considered by customers in choosing products Simpeda savings on PT . Sengata Kaltim Bank Branch , which consists of product value factors , value of service , personnel value , and the value of the image . It is proven based on the results of a questionnaire in which the respondents chose the answer